Assessing the Program Experiences and Employment Outcomes of Notre Dame of Jolo College BSIT Graduates - Acevedo, Edgar Jansol; Matriz, Marcilyn Lee (European Scientific Journal, ESJ, 2025)
This tracer study investigated the program experiences and employment outcomes of the Bachelor of Science in Information Technology (BSIT) graduates from 2017 to 2019 to assess career readiness and identify areas for improvement. Using a descriptive survey method and convenience sampling, data were collected from 58 graduates and analyzed using descriptive statistics. Results indicated that most graduates preferred institutions offering holistic education and programs with adequate resources and qualified staff. Many secured non-permanent, rank-and-file positions in the government sector within six months and remained in these roles for over a year while earning below the median monthly salary. Graduates expressed satisfaction with teaching methods, study conditions, guidance, and competency attainment, crediting hands-on training for their employment readiness. They found their acquired competencies useful in their current jobs and were guided by the core institutional values of faith, respect, and commitment. The study concluded that graduates had a positive perception of their educational experiences and recognized the program’s role in their employment opportunities. Nonetheless, areas such as written works, self-study activities, study habits, communication skills, problem analysis, and job orientation should be strengthened to enhance students’ workforce readiness.